The Consequences of Changing Curriculum Structures on the Professional Identity and Consciousness of Teacher Educators - Chamo, Nurit; Biberman-Shalev, Liat; Broza, Orit (Journal of Ecohumanism, 2024)
This study investigates the impact of a curricular-structural change implemented in a teacher training institution during the post-COVID-19 era, involving a shift to Blended Learning. Focused on 76 teacher-educators and 553 students, the research utilizes qualitative methods to analyze perceptions of this change and its consequences on professional identity. Results reveal a nuanced reflective discourse, delineated into three sequential turns: tactical, conceptual, and strategic. These turns underscore transformative expressions in teacher-educators’ professional identity, emphasizing the imperative to delve into curricular dimensions. Notably, the study highlights the need for sustained inquiry into fundamental educational questions, particularly in the context of diverse learning environments associated with Blended Learning. This research illuminates the potential of such environments in supporting overarching educational goals and underscores the imperative for continued exploration in this learning and instruction domain.